Rethinking conformity and imitation: divergence, convergence, and social understanding - Hodges, Bert H. (Frontiers in Psychology, 2014)
Social and developmental psychologists have stressed the pervasiveness and strength of humans’ tendencies to conform and to imitate, and social anthropologists have argued that these tendencies are crucial to the formation of cultures. Research from four domains is reviewed and elaborated to show that divergence is also pervasive and potent, and is interwoven with convergence in a complex set of dynamics that is often unnoticed or minimized. First, classic research in social conformity is reinterpreted in terms of truth, trust, and social solidarity, revealing that dissent is its most salient feature. Second, recent studies of children’s use of testimony to guide action reveal a surprisingly sophisticated balance of trust and prudence, and a concern for truth and charity. Third, new experiments indicate that people diverge from others even under conditions where conformity seems assured. Fourth, current studies of imitation provide strong evidence that children are both selective and faithful in who, what, and why they follow others. All of the evidence reviewed points toward children and adults as being engaged, embodied partners with others, motivated to learn and understand the world, others, and themselves in ways that go beyond goals and rules, prediction and control. Even young children act as if they are in a dialogical relationship with others and the world, rather than acting as if they are solo explorers or blind followers. Overall, the evidence supports the hypothesis that social understanding cannot be reduced to convergence or divergence, but includes ongoing activities that seek greater comprehensiveness and complexity in the ability to act and interact effectively, appropriately, and with integrity.